Investigation into the Effect of Aspartame on the Expression of p53 and BAX in Mouse Stomach Tissue - Angelique Cheryl; Aoife Mac Cooey (SURE Journal: (Science Undergraduate Research Experience Journal))
Introduction: The recent reclassification of aspartame as a Group 2B hazard by the International Agency for Research on Cancer, along with studies suggesting links to cancer, has raised concerns and prompted further investigation. Evidence suggests that aspartame exposure may alter p53 and BAX gene expression, affecting apoptosis in cancer cells. This study aims to examine how aspartame exposure affects p53 and BAX gene expression in normal mouse stomach tissue, shedding light on cellular stress and apoptosis mechanisms. Methods: Mice were sacrificed, and stomach tissue was excised and divided into control and treatment groups. RNA extraction was carried out in the control and aspartame-treated mouse stomach tissue. The expression of 2 target genes (p53 and BAX) and 2 potential housekeeping genes (UBC and beta-actin) were determined using PCR and qPCR. The statistical significance of the relative fold changes was assessed with two-sample t-tests in Microsoft Excel. Findings: Treatment with 1mg/ml of aspartame resulted in the upregulation of p53 and BAX, along with the downregulation of UBC relative to the control untreated mouse stomach tissue. Conclusion: In conclusion, these preliminary findings demonstrate that exposure to high concentrations of aspartame (1mg/ml), equivalent to the upper limit of the ADI of 40 mg/kg body weight, significantly upregulated p53 and BAX. This implies a possible connection between aspartame exposure and cellular stress, including increased apoptosis signalling, potentially contributing to cancer development, especially via BAX. However, limitations include small sample size and challenges associated with poor RNA quality, which could have influenced the results.